2023
DOI: 10.1186/s13048-023-01114-4
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A and bisphenol S both disrupt ovine granulosa cell steroidogenesis but through different molecular pathways

Abstract: Background Ovarian granulosa cells (GC) are essential for the development and maturation of a proper oocyte. GC are sensitive to endocrine disruptors, including bisphenol A (BPA) and its analogue bisphenol S (BPS), plasticisers present in everyday consumer products. BPA exhibits greater binding affinity for the membrane oestrogen receptor (GPER) than for the nuclear oestrogen receptors (ERα and ERβ). Here, we analysed the effects of BPA and BPS on the steroidogenesis of ovine GC in vitro, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 84 publications
0
3
0
2
Order By: Relevance
“…While their impact on fertility is less well studied, initial reports indicate they also exhibit negative effects on reproductive functions, albeit through distinct intracellular pathways and mechanisms compared to BPA ( Rochester and Bolden, 2015 ; Abouhamzeh et al , 2023 ). In various animal models, BPS has been shown to disrupt granulosa cell steroidogenesis ( Téteau et al , 2020 , 2023 ), impair the in vitro early developmental competence of oocytes and embryos ( Desmarchais et al , 2020 ; Žalmanová et al , 2023 ) and reduce the motility of spermatozoa ( Torres-Badia et al , 2023 ; Téteau et al , 2023 ). Similarly, BPF has been shown to affect motility, capacitation, and mitochondrial membrane potential in cryopreserved bovine sperm ( Nguyen et al , 2022 ; Davis et al , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…While their impact on fertility is less well studied, initial reports indicate they also exhibit negative effects on reproductive functions, albeit through distinct intracellular pathways and mechanisms compared to BPA ( Rochester and Bolden, 2015 ; Abouhamzeh et al , 2023 ). In various animal models, BPS has been shown to disrupt granulosa cell steroidogenesis ( Téteau et al , 2020 , 2023 ), impair the in vitro early developmental competence of oocytes and embryos ( Desmarchais et al , 2020 ; Žalmanová et al , 2023 ) and reduce the motility of spermatozoa ( Torres-Badia et al , 2023 ; Téteau et al , 2023 ). Similarly, BPF has been shown to affect motility, capacitation, and mitochondrial membrane potential in cryopreserved bovine sperm ( Nguyen et al , 2022 ; Davis et al , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, the tumorigenic phenotype in immunodeficient mice is displayed by exogenous expression of c-Fos in non-tumorigenic HNSCC MDA1386Tu cells. Overall, in non-tumorigenic cell lines, they have demonstrated that overexpression of c-Fos makes the cells tumorigenic and increases the expression of EMT/CSC marker genes [27]. A study by, Hearn et al, 2020 proposed the germline HSD3B1 genotype as a genetic biomarker of resistance to Androgen Deprivation Therapy (ADT) for prostate cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…В світовій промисловості найбільшого поширення, із групи ендокринних руйнівників, набув Бісфенол А [5]. На теперішній час проведено ряд досліджень по виявленню патологічного впливу речовин з ендокринними властивостями на складні механізми сперматогенезу [6]. Дослідним шляхом доведено, що вплив високих доз ВРА викликав у чоловіків апоптоз клітин Лейдіга та ряд гістопатологічних змін в сім'яниках, включаючи редиціювання шарів сперматогенного епітелію, збільшення маси тіла, зменшення маси сім'яників та дисфункцію сперматогенезу, яка проявлялась значно пізніше після періоду впливу ВРА [7].…”
Section: постановка проблемиunclassified
“…Щури самців, які піддавалися дії BPA в період пренатального та постнатального розвитку, мали низьку масу сім'яників та низький рівень тестостерону у дорослому віці [8]. Загалом, складність репродуктивної функції робить її вразливою до негативного впливу найбільш поширеного з групи ендокринних дизрапторівбісфенолу А, зумовлює актуальність вивчення цієї медичної та соціальної проблеми, а розробка заходів прогнозування наслідків впливу, профілактики та лікування порушень репродуктивного здоров'я набуває особливої соціальної цінності при розробці моделі надання медичної допомоги чоловікам, які страждають на безпліддя [6].…”
Section: постановка проблемиunclassified